Homo faber як homo viator: модерна та постмодерна візії (на матеріалі лірики Лесі Українки та Оксани Забужко) - Калинюшко, Олеся; Kalуnіushko, Olesia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на основі порівняльного аналізу лірики Лесі Українки та Оксани Забужко встановлено залежність характеру мандрів героїнь від специфіки образу митця, сформованого в епохи модернізму та постмодернізму відповідно. Простежено, що модерна доба, возвеличуючи постать homo faber(a), представ- ляє мандри як шлях його духовного становлення, підтвердження стійкості та внутрішньої сили, натомість постмодерна епоха, переосмислюючи роль митця, на чільне місце виводить homo viator(a), який, трансформуючись у номада, репрезентує образ дезорієнтованого індивіда, позбавленого могутності модер- ного митця-проводиря. The article determines the dependence of character’s travelling pattern on the artist’s image specificity formed by the modernism and postmodernism respectively. The investigation has been based on the comparative analysis of poetry by Lesia Ukrainka and Oksana Zabuzhko. It has been traced that modern epoch, extoling the homo faber, presents journey as a way to his/her spiritual maturing, confirmation of firmness and inner strength. At the same time postmodern era, reconsidering artist’s role, raises homo viator that transforming into nomad represents image of disoriented individual deprived of modernistic artist-leader’s might. The ways in which female characters implement their artistic potential and simply are heard while the artist is praised or decanonized have been contrasted. Lesia Ukrainka articulates poet’s messianic destination. Oksana Zabuzhko, on the contrary, represents her lyric character as a part of the crowd introducing into the poetry image of so called “lyric we” or concealing by humour and irony.
Homo Faber as Homo Viator: Modern and Postmodern Visions (Lesia Ukrainka and Oksana Zabuzhko’s Poetry)
Keywords: Леся Українка; homo faber; Оксана Забужко; homo viator; мандри; дім; номад; модернізм; постмодернізм; Lesia Ukrainka; Oksana Zabuzhko; homo faber; homo viator; wanderings; nomad; modernism; postmodernism